5/3 can be subtracted from both sides as follows:
(5/3)x + 11/3 - 5/3 = -4/3 - 5/3
Simplifying on the left side:
(5/3)x + 11/3 - 5/3 = (5/3)x + 6/3
= (5/3)x + 2
On the right side:
-4/3 - 5/3 = -9/3 = -3
So, the equation becomes:
(5/3)x + 2 = -3
Now, in order to solve for x, we can multiply both sides of the equation by the reciprocal of 5/3, which is 3/5:
(3/5)((5/3)x + 2) = (3/5)(-3)
Simplifying on the left side:
(3/5)((5/3)x + 2) = (3/5)(5/3)x + (3/5)(2)
= (1)x + (6/5)
= x + 6/5
On the right side:
(3/5)(-3) = -9/5
So, the equation becomes:
x + 6/5 = -9/5
Therefore, the solution is x = -9/5 - 6/5 = -15/5 = -3.
The equation 5/3x+11/3=-4/3 is solved as follows fill in the correct numbers to complete the solution
5/3x+11/3=-4/3
5/3=? Subtract from both sides
X=? Multiple both sides by 3/5 the reciprocal of 5/3
1 answer